Efficient Sensor Interfaces, Advanced Amplifiers and Low Power RF Systems Advances in Analog Circuit Design 2015 - Makinwa, Kofi A.A; Baschirotto, Andrea; Harpe, Pieter (Springer International Publishing : Imprint: Springer, 2016)
This book is based on the 18 tutorials presented during the 24th workshop on Advances in Analog Circuit Design. Expert designers present readers with information about a variety of topics at the frontier of analog circuit design, including low-power and energy-efficient analog electronics, with specific contributions focusing on the design of efficient sensor interfaces and low-power RF systems. This book serves as a valuable reference to the state-of-the-art, for anyone involved in analog circuit research and development. ·         Provides a state-of-the-art reference in analog circuit design, written by experts from industry and academia; ·         Presents material in a tutorial-based format; ·         Includes coverage of high-performance analog-to-digital and digital to analog converters, integrated circuit design in scaled technologies, and time-domain signal processing.